Assessment of the Attributional Styles of High- and Low-grade Point Medical Students at Isfahan University of Medical Sciences: A Cross-sectional and Descriptive Study - Padideh Daneii; Vida Sarmadi; Negin Mahmoudi; Amir Kian Moaveni; Fatemeh Mohammad Alizadeh; Sina Neshat; Armindokht Shahsanaee (Shiraz University of Medical Sciences, 2022)
Background : Academic failure is one of the most important issues for both family and students. It has many adverse consequences on students' mental health. Therefore, understanding the factors that influence academic achievement can help reduce academic failure and thus improve students' physical, mental, and educational status. This study aimed to investigate the relationship between students' attributional styles and academic achievement in medical students at Isfahan University of Medical Sciences. Methods: The present study has a cross-sectional and descriptive-analytical design. Cronbach's alpha coefficient confirmed the reliability of the ASQ (Attributional Styles Questionnaire) questionnaire for each subscale . The sampling method in this study was census and consisted of 76 First- and Seven- Semester medical students at Isfahan University of Medical Sciences. In this study, Attributional Styles Questionnaire (ASQ) was used to measure attributional styles. Descriptive statistics and independent sample t-test were used through SPSS software version 25 for data analysis. Results: The results showed there is a significant relationship between  optimistic and pessimistic attributions and academic achievement. In terms of the overall score of the questionnaire, positive and negative attributions were significantly higher in medical students with higher grade point averages than students with lower grade point averages and academic probation (P <0.05). Conclusion: It can be concluded that there is a significant relationship between the medical students' attribution styles at Isfahan University of Medical Sciences and their academic achievement.